2018
DOI: 10.1038/s41467-018-03181-4
|View full text |Cite
|
Sign up to set email alerts
|

Effector CD4+ T cells recognize intravascular antigen presented by patrolling monocytes

Abstract: Although effector CD4+ T cells readily respond to antigen outside the vasculature, how they respond to intravascular antigens is unknown. Here we show the process of intravascular antigen recognition using intravital multiphoton microscopy of glomeruli. CD4+ T cells undergo intravascular migration within uninflamed glomeruli. Similarly, while MHCII is not expressed by intrinsic glomerular cells, intravascular MHCII-expressing immune cells patrol glomerular capillaries, interacting with CD4+ T cells. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 67 publications
(125 reference statements)
3
42
0
Order By: Relevance
“…While presentation of tumor Ags is generally thought to occur within primary tumor sites or their draining lymph nodes, a recent report demonstrated that intravascular MHCII + monocytes are able to present Ag to CD4 + T cells within inflamed glomeruli vasculature . Whether similar interactions between T cells and monocytes can occur within tumor vasculature or following engulfment of tumor‐derived material in circulation remains an interesting direction for further exploration.…”
Section: Functions In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…While presentation of tumor Ags is generally thought to occur within primary tumor sites or their draining lymph nodes, a recent report demonstrated that intravascular MHCII + monocytes are able to present Ag to CD4 + T cells within inflamed glomeruli vasculature . Whether similar interactions between T cells and monocytes can occur within tumor vasculature or following engulfment of tumor‐derived material in circulation remains an interesting direction for further exploration.…”
Section: Functions In Cancermentioning
confidence: 99%
“…82 While presentation of tumor Ags is generally thought to occur within primary tumor sites or their draining lymph nodes, a recent report demonstrated that intravascular MHCII + monocytes are able to present Ag to CD4 + T cells within inflamed glomeruli vasculature. 84…”
Section: Ag Presentationmentioning
confidence: 99%
“…NETs are released within the microvasulature, where they not only contribute to endothelial injury but also may activate TLRs expressed on resident tissue cells (48,56) and may promote local alternate complement pathway activation (57). They also deposit the autoantigens MPO and PR3 in target tissues, making them potentially able to be presented to effector antigen-specific T cells (58). While mechanistic understanding of NETs has largely been gleaned from in vitro studies (54,59), the functional role of NETs as effectors of injury has also been translated to animal models of AAV.…”
Section: Transfer Of Anti-mpo Antibodiesmentioning
confidence: 99%
“…Glomerular injury is mild to minimal after transfer of cells specific to an irrelevant specificity (ovalbumin) (18,20). Antigen can be presented intravascularly by patrolling monocytes (58) and may also be presented locally by glomerular endothelial cells, while later in disease dendritic cells infiltrate diseased glomeruli in human AAV (82).…”
Section: Transfer Of Effector Cd4+ or Cd8+ T Cellsmentioning
confidence: 99%
“…103 On the other hand, uptake of bacteria by resident macrophages may actually impede the development of an adaptive immune response during UTI, as the depletion of these cells was shown to enhance bacterial uptake by dendritic cells and reduce bacterial burden upon secondary challenge. 104 IVM has been utilized to investigate immunologic responses in the urinary tract [105][106][107][108][109][110][111][112] ; however, studies focused on infection are more limited. [113][114][115][116] IVM has helped elucidate the mechanisms that underlie leukocyte recruitment dynamics to the bladder 113 and pathophysiology in the kidneys [114][115][116] during infection with Escherichia coli.…”
Section: Localized Infections: Imaging the Urinary Tractmentioning
confidence: 99%